Synthesis of amphiphilic meso-tetrasubstituted porphyrin-L-amino acid and -heterocyclic conjugates based on m-THPP. - Senge, Mathias (My University, 2018)
Two series of amphiphilic meso-tetrasubstituted porphyrin conjugates based on 5,10,15,20-tetrakis(3-hydroxyphenyl)porphyrin (m-THPP) covalently linked to L-amino acids and heterocycles were synthesized efficiently in the context of a program targeting new photosensitizers for PDT. 5, 10, 15-Tris(3-hydroxyphenyl)-20-(3-oxyacetic acid)phenyl]porphyrin and the respective trihexyl ether derivatives were conjugated with polar and non-polar natural L-amino acids such as glycine, L-proline, and L-tyrosine via an amide bond linker using N, N, N', N'-tetramethyl-O-(1H-benzotriazol-1-yl)uroniumhexafluorophosphate in diisopropylethylamine (HBTU/DIPEA). m-THPP was also conjugated with heterocyclic systems such as indole 3-acetic acid, 4-methylthiazole-5-carboxylic acid, and thiophene-2-carboxylic acid via ester linker using N-(3-dimethylaminopropyl)-N'-ethylcarbodiimide hydrochloride in N-hydroxysuccinamide or 1-hydroxybenzotriazole (EDCI, NHS or HOBt). The members of the two series were obtained in good yields and characterized by UV-vis, HRMS MALDI-TOF, 1H NMR and 13C NMR spectroscopy.
PUBLISHED
Keywords: Synthesis; Amphiphilic meso-tetrasubstituted porphyrin conjugates; L-amino acid; Heterocycles; Photodynamic therapy